Pobhinci-bhinciki kuli: An accounting research methodology based on the cultural philosophy of the butonese people - Endiaverni, Wa Ode; Triyuwono, Iwan; Mulawarman, Aji Dedi (The Indonesian Accounting Review, 2024)
This research aims to develop an accounting research methodology based on the cultural philosophy of the Butonese people, “pobhinci-bhinciki kuli”. In the Wolio language (Buton Sultanate), pobhinci-bhinciki kuli means pinching each other’s skin or feeling like they are in the same boat. This research uses a literature review method. Validity is confirmed through interviews with Butonese cultural figures, sociologists, anthropologists and writers. The findings indicate that research methodology developed from local wisdom can be used to produce research that is more holistic in describing the reality of Indonesian society. The Butonese people’s philosophy of life “pobhinci-bhinciki kuli” upholds purity of feeling, as an indicator. The feeling in question is a divine feeling that is continuously felt and pursued through kangkilo (purity). Therefore, the scientific implications of using pobhinci-bhinciki kuli will return to the authenticity of the local wisdom of Indonesian society which is always oriented towards the main value of purity in moving towards true divinity by prioritizing the integrity of reality. The achievements of science are not only rational but united and moving in the purity of awareness of holiness in its theoretical, research and empirical forms in accounting research methodology.